2022
DOI: 10.3390/su14148300
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Monitoring the Psychological Wellbeing and Mental Health of Nursing Staff for Sustainable Management

Abstract: This study examines the psychological wellbeing and mental health of nursing staff and determines workplace factors that affect them. Wellbeing and sustainable workload are important for the quality of work life. A cross-sectional study of employees in nursing was conducted at Slovenian hospitals. The response was 35%. The main findings were that more than half of employees are satisfied or very satisfied with their job and with their leaders’ support, but they are often exposed to stress. Quality of work life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
(61 reference statements)
1
6
0
Order By: Relevance
“…Healthcare management must be aware that constantly monitoring and improving employees' work-life quality in nursing is necessary because work-life quality is associated with well-being at the workplace and work satisfaction. These results are in comparison with the results from Slovenia, which reported that work-life quality is associated with the psychological well-being and mental health of employees in nursing [57]. We also agree with Abdesalam et al [58], who noted that healthcare system reforms are required to improve work-life quality and well-being at the workplace in nursing.…”
Section: Discussionsupporting
confidence: 89%
“…Healthcare management must be aware that constantly monitoring and improving employees' work-life quality in nursing is necessary because work-life quality is associated with well-being at the workplace and work satisfaction. These results are in comparison with the results from Slovenia, which reported that work-life quality is associated with the psychological well-being and mental health of employees in nursing [57]. We also agree with Abdesalam et al [58], who noted that healthcare system reforms are required to improve work-life quality and well-being at the workplace in nursing.…”
Section: Discussionsupporting
confidence: 89%
“…The QWL comprises several aspects, including job satisfaction, work-related stress, workload, organizational support, and the general well-being of healthcare employees [6]. In the context of nurses working in settings marked by humanitarian crises and healthcare delivery to marginalized people, comprehending the determinants that impact their QWL is not just a question of professional significance but also an ethical obligation [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is essential to acknowledge the intricate and challenging circumstances under which healthcare personnel function inside Syrian refugee camps [4]. The healthcare worker above encounter various problems that substantially influence the quality of their professional experiences and their capacity to provide efficient treatment [7]. The challenges faced by healthcare professionals in emergency and critical care settings include factors such as a significant influx of patients, scarcity of resources [3], regular exposure to traumatic and distressing circumstances [7,8], difficulties arising from language and cultural differences [9], and the demanding nature of emergency and critical care services [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations